Probabilitas dan determinan pemanfaatan asuransi kesehatan di Indonesia (berdasarkan data IFLS tahun 2015) - Miftakhun Nafisah Yannis Putri; Pujianto Pujianto (Berita Kedokteran Masyarakat (BKM), 2019)
The probability and determinants of the utilization of health insurance in Indonesia: analysis of 2015 IFLS data Purpose: This study investigates the probability and the determinants of use of health insurance in Indonesia.Method: The Indonesian Family Life Survey (IFLS) 2015 data were used and analyzed by logistic regression/probit. Age, gender, marital status, family status, education, employment status, and area of residence were used as determinant variables.Results: The proportion of utilization of health insurance is 39.9%. A total of 60.02% of health insurance owners do not use health insurance and issueout of pocket (OOP) fees. Age variables (0.037), education (0,000) and residential areas (0,000) were significantly significant (p-value <0.05) for the use of health insurance.